Detection of pneumonia from chest X-ray images using machine learning - Priya, Afsana Rahman; Sarkar, Kashmira; Khan, Tania Rahman; Turna, Sohani Fatehin; Mubashshira, Sadia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.